Writing the Great War the historiography of World War I from 1918 to the present - Cornelißen, Christoph 1958-; Weinrich, Arndt 1979- (Berghahn, 2021)
"From the Treaty of Versailles to the 2018 centenary and beyond, the history of the First World War has been continually written and rewritten, studied and contested, producing a rich historiography shaped by the social and cultural circumstances of its creation. Writing the Great War provides a groundbreaking survey of this vast body of work, assembling contributions on a variety of national and regional historiographies from some of the most prominent scholars in the field. By analyzing perceptions of the war in contexts ranging from Nazi Germany to India's struggle for independence, this is an illuminating collective study of the complex interplay of memory and history"
Keywords: Geschichte 1914-2019; Erster Weltkrieg; Geschichtsschreibung; World War, 1914-1918 / Historiography; World War, 1914-1918 / Influence; World War, 1914-1918 / Centennial celebrations, etc; Collective memory; Konferenzschrift -- 2012 -- Paris